Microstructure characteristics and performance optimization of (Ti,Nb)C particle reinforced Fe-based materials by laser melting deposition - LI Qingtang; ZHANG Yuchen; WU Hairong (Fenmo yejin jishu, 2025)
The (Ti,Nb)C composite carbide particle-reinforced phases were obtained in the Fe-based materials by laser melting deposition method. The microstructure characteristics and interface formation mechanism of the (Ti,Nb)C particle-reinforced Fe-based materials were studied, and the influence of laser heat input on the carbide precipitation were analyzed. On this basis, the mechanical properties of the (Ti,Nb)C particle-reinforced Fe-based materials were optimized by adjusting the processing parameters. The results show that the phases of the Fe-based materials reinforced by (Ti,Nb)C particles are mainly composed of the α-Fe matrix and (Ti,Nb)C composite carbide reinforced particles. The α-Fe grains and (Ti,Nb)C carbides show the well-matched interfacial orientation through the combination of low-index crystal planes. Meanwhile, with the increase of heat input, the size and the area ratio of (Ti,Nb)C particles in the materials increase significantly. The tensile strength of the (Ti,Nb)C particle-reinforced Fe-based materials shows a trend of increasing first and then decreasing with the increase of heat input. When the heat input is 105 J·mm−2, the tensile strength is the maximum, which is 653 MPa. It can be seen from the tensile stress-strain curves and microstructure of the fracture surface that the (Ti,Nb)C particle-reinforced Fe-based materials exhibit good toughness. The (Ti,Nb)C composite carbide particles subjected to external loading can absorb and disperse stress, hinder the propagation of dislocations and cracks, thereby achieving the effect of enhancing the mechanical properties of the materials.